2021
DOI: 10.3390/pathogens10101223
|View full text |Cite
|
Sign up to set email alerts
|

Q Fever Vaccine Development: Current Strategies and Future Considerations

Abstract: Q fever is a zoonotic disease caused by the intracellular pathogen Coxiella burnetii. This disease typically manifests as a self-limiting, febrile illness known as acute Q fever. Due to the aerosol transmissibility, environmental persistence, and infectivity of C. burnetii, this pathogen is a notable bioterrorism threat. Despite extensive efforts to develop next-generation human Q fever vaccines, only one vaccine, Q-Vax®, is commercially available. Q-Vax® is a phase I whole-cell vaccine, and its licensed use i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 96 publications
0
11
0
Order By: Relevance
“…7 In humans, Q-VAX vaccination induces both antibodies and cellular immune responses, but cellular immunity was a more reliable correlate of long-term protection in Australian clinical trials. 6 Consistent with a central role for cellular immunity in controlling Cb infection, 2 , 5 adoptive transfer of lymphocytes or CD4 + T cells from Sol II-vaccinated mice conferred partial protection to naive animals, whereas passive transfer of immune sera did not. 1 Previous studies have demonstrated protection of naive mice by immune antibodies from WCV-vaccinated animals, 9 and whether failure of Sol II-immune sera to confer similar protection arose from differences in antibody quality or quantity remains unknown.…”
Section: Main Textmentioning
confidence: 82%
See 2 more Smart Citations
“…7 In humans, Q-VAX vaccination induces both antibodies and cellular immune responses, but cellular immunity was a more reliable correlate of long-term protection in Australian clinical trials. 6 Consistent with a central role for cellular immunity in controlling Cb infection, 2 , 5 adoptive transfer of lymphocytes or CD4 + T cells from Sol II-vaccinated mice conferred partial protection to naive animals, whereas passive transfer of immune sera did not. 1 Previous studies have demonstrated protection of naive mice by immune antibodies from WCV-vaccinated animals, 9 and whether failure of Sol II-immune sera to confer similar protection arose from differences in antibody quality or quantity remains unknown.…”
Section: Main Textmentioning
confidence: 82%
“…Cb virulence varies with differences in lipopolysaccharide (LPS) structure; all virulent strains (including the isolate used in Q-VAX) express full-length “phase I” LPS, while truncation to “phase II” LPS leads to a loss of virulence. 5 Sol II is derived from an avirulent phase II Cb strain and can be produced under lower biocontainment. 1 Although previous phase II-derived vaccine candidates demonstrated limited or no efficacy in preclinical testing, 5 Sol II vaccination conferred significant protection in mouse, guinea pig, and macaque models of Cb aerosol challenge, albeit with somewhat lower efficacy than did a WCV or a phase I soluble extract (Sol I) under the dosing regimens employed.…”
Section: Main Textmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on these previous epitope profiling data, we generated multiple viral vector-based vaccine candidates expressing epitope concatemers designed to establish anti- C. burnetii cellular immunity in humans. Vaccine development requires establishing immune response correlates in animal models that can inform selection of safe and effective vaccine doses for human testing ( 24 , 25 ). To this end, we tested the vaccine candidates in three established animal models of immune responses to C. burnetii .…”
Section: Introductionmentioning
confidence: 99%
“…Intradermal skin testing was implemented in the late 1950s to assess prior exposure to C. burnetii , but skin testing is not completely reliable and can be expensive and cumbersome to implement ( Schoffelen et al., 2014 ). An equally efficacious and less reactogenic vaccine is needed to eliminate the need for pre-screening and to broaden vaccination efforts in light of both natural outbreaks and biodefense applications ( Long, 2021 ).…”
Section: Introductionmentioning
confidence: 99%